KEBERAGAMAN PESERTA DIDIK DAN PERAN PEMBELAJARAN BERDIFERENSIASI DALAM PEMENUHAN TARGET KURIKULUM - Romadani, Moh. Nafis Husen; Elisabeth Pratidhina Founda Noviani (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2024)
In the 21st century, education demands a transition from teacher-centered to student-centered methodologies. This shift is essential for equipping students with key 21st-century competencies, commonly known as the 4Cs (Communication, Collaboration, Critical Thinking, and Creativity). To foster these skills, educators must support students with diverse characteristics in achieving proficiency in the 4Cs. Differentiated instruction is an educational strategy designed to address the unique needs, interests, and abilities of students within a classroom. This approach involves adapting the content, process, products, and learning environment to facilitate optimal learning for each student. Differentiated instruction is an ideal model for students, as it enables the enhancement of their potential in alignment with individual learning needs, including personal interests, learning readiness, and learning profiles. The aim of this article is to explore how differentiated instruction aligns with and supports the curriculum objectives in Indonesian education.This research is descriptive and involves the collection of various relevant references on differentiated instruction. The study employs a literature review method, which includes a theoretical analysis of multiple references related to scientific literature. The findings from this research indicate that differentiated instruction can accommodate the needs of each student, making it a highly suitable method for meeting the targets of the Merdeka curriculum